2005
DOI: 10.1021/ja053557t
|View full text |Cite
|
Sign up to set email alerts
|

Charged Polypeptide Vesicles with Controllable Diameter

Abstract: We report the preparation and characterization of charged, amphiphilic block copolypeptides that form stable vesicles and micelles in aqueous solution. Specifically, we prepared and studied the aqueous self-assembly of a series of poly(L-lysine)-b-poly(L-leucine) block copolypeptides, KxLy, where x ranged from 20 to 80 and y ranged from 10 to 30 residues, as well as the poly(L-glutamatic acid)-b-poly(L-leucine) block copolypeptide, E60L20. Furthermore, the vesicular assemblies show dynamic properties, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
338
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 345 publications
(342 citation statements)
references
References 31 publications
3
338
0
1
Order By: Relevance
“…A key feature of this work is the utilization of short polyelectrolyte segments, which limits such polyion complex formation in dilute solutions. copolypeptide, E 60 L 20 [84]. In other work, it was found that samples with high K to L molar ratios (e.g.…”
Section: Copolypeptide Vesiclesmentioning
confidence: 93%
“…A key feature of this work is the utilization of short polyelectrolyte segments, which limits such polyion complex formation in dilute solutions. copolypeptide, E 60 L 20 [84]. In other work, it was found that samples with high K to L molar ratios (e.g.…”
Section: Copolypeptide Vesiclesmentioning
confidence: 93%
“…[106] Oppositely charged ionic diblock copolymers based on poly(aspartate)-PEO formed semi-permeable vesicles that were christened 'PICsomes', [107] which could reversibly bind oxygen using encapsulated myoglobin. [108] More recently, so-called peptosomes have been developed from copolymers comprising both hydrophilic and hydrophobic polypeptide chains, [102,109] which can be used as intracellular cell delivery vehicles for both dyes [103] and DNA. [110,111] Lecommandoux and co-workers reported the pH-responsive 'schizophrenic' nature of vesicles formed from poly(glutamic acid)-poly(lysine) copolypeptides, which offer a different surface chemistry depending on the solution pH.…”
Section: Reactive and Environmentally Responsive Membranes For Delivementioning
confidence: 99%
“…In general, the helical, rod-like nature of the peptide results in a flatter interface, which favors vesicle of fibril formation. [77][78][79][80][81][82][83][84][85] FIGURE 5 R h vs. pH plots for PB 107 [83][84][85] In their research, they studied assemblies formed from poly(c-benzyl-L-glutamate) 23 -b-hyaluronan 10 (PBLG 23 -b-HYA 10 , polypeptide-bpolysaccharide) polysaccharide. They denote that the PBLG block was chosen to guarantee the formation of vesicles, whereby its rigid, helical nature leads to close packing of helices which serves to favor flatter interface morphologies (Fig.…”
Section: Assemblies Composed Of Hydrophobic Peptide Coresmentioning
confidence: 99%
“…81,86 Other reports in literature have shown vesicle formation for copolypeptide amphiphiles that contain two blocks of naturally occurring amino acids; one block being a rod-like, hydrophobic helix and the other a polyelectrolyte serving to stabilize the assembly through electrostatic interaction with water. 75,[78][79][80]82,87 Deming and coworkers have performed seminal work in this area, and the physical behavior of these vesicle-forming copolypeptides is well illustrated through their work. For example, they studied the aggregation behavior of PLys-b-poly(L-leucine) (PLys-b-PLLeu) copolymers; the PLeu was employed as due to its hydrophobicity and its ability to form stable helices.…”
Section: Assemblies Composed Of Hydrophobic Peptide Coresmentioning
confidence: 99%